Integrated view on a eukaryotic osmoregulation system - Hohmann, Stefan (Henry Stewart Talks, 2014)
Osmoregulation, Cell compression and macromolecular crowding, Osmolyte accumulation, Metabolism and signalling, Modelling, simulation and prediction, Multi-level control of osmolyte accumulation, Mitogen activated protein kinase signalling, Signalling crosstalk, Synthetic biology approaches to osmoregulation